2003
DOI: 10.1159/000070285
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Low-Dose Docetaxel in Advanced Hormone-Resistant Prostate Cancer Patients Previously Exposed to Chemotherapy

Abstract: Objective: The aim of this study was to evaluate the activity and tolerability of docetaxel in patients with hormone-resistant prostate cancer previously exposed to chemotherapy. Methods: We enrolled 27 patients with hormone-resistant prostatic cancer that had progressed during first-line chemotherapy. The primary end-point was palliative response defined as a 2-point reduction in the 6-point present pain intensity scale, and an improvement in Karnofsky performance status of one 10-point category. The treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Weekly administration of docetaxel has been shown to have similar efficacy with less neutropenia than 3-weekly schedules [15]. Several phase II studies in CRPC have investigated weekly docetaxel, given at doses of 25–40 mg/m 2 in a variety of schedules [16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Weekly administration of docetaxel has been shown to have similar efficacy with less neutropenia than 3-weekly schedules [15]. Several phase II studies in CRPC have investigated weekly docetaxel, given at doses of 25–40 mg/m 2 in a variety of schedules [16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…This indicates that tolerability of the present protocol is acceptable in a population that is often elderly. The major contribution of the chemotherapy in HRPC is improvement in the quality of life, particularly with respect to pain relief [3, 4, 18]. Beer et al [14]have previously reported that docetaxel alone helped to improve pain significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Reason for exclusion Mattioli (1998) 189 Not an RCT MedlinePlus (2005) 190 Background Miller (2002) 191 Not an RCT Miller (2003) 192 Not an RCT Montero (2005) 193 Background Moore (1994) 194 Not an RCT Muthuramalingam (2004) 9 Background Nabhan (2005) 195 Background National Cancer Institute (1999) 196Background National Institute for Clinical Excellence (2002) 8 Background Newling (1999) 225 Commentary/overview Office for National Statistics (2002) 3 Background Oh (2000) 226 Commentary/overview Oh (1998) 227 Commentary/overview Olson (2000) 228 Commentary/overview Parmar (1998) 25 Background Parvez (2003) 229 Commentary/overview Petrioli (2003) 230 Not an RCT Petrylak (1999) 231 Commentary/overview Petrylak (2000) 232 Commentary/overview Petrylak (2000) 233 Not an RCT Petrylak (2002) 13 Background Petrylak (2002) 234 Commentary/overview Picus (1999) 235 Commentary/overview Picus (1999) 236 Not an RCT Pozzessere (2002) 237 Not an RCT Price (2004) 238 Commentary/overview Raghavan (2002) 239 Not an RCT Rago (2003) 240 Not an RCT Rajasenan (2001) 241 Not an RCT Rexer (2004) 242 Commentary/overview 244 Wrong patient group Rosenthal (2000) …”
Section: Study Detailsmentioning
confidence: 99%